Overweight adolescents eat what? and when? analysis of consumption patterns to guide dietary message development for intervention - Smith, Kyla; Straker, Leon; Kerr, Deborah; Smith, Anne (Wiley-Blackwell Publishing Ltd., 2014)
Background: Little is known about overweight adolescent dietary consumption patterns, with challenges to collecting meaningful data making it difficult to develop targeted obesity interventions. The present study aimed to examine the timing and consumption of fruit, vegetables and junk food by time of the day and day of the week. Methods: Overweight adolescents (n = 61), aged 12–16 years, completed 3-day food records. Negative binomial and binary logistic regression using generalised estimating equations were used to compare the amount and likelihood of the consumption of each food group between time periods. Results: Overweight adolescent girls were more likely to eat fruit on weekdays than weekends [odds ratio (OR) = 5.0. P < 0.001], as were boys (OR = 2.5, P = 0.034). Adolescents consumed more fruit at school than other meals [girls: incident rate ratio (IRR) = 7.5, P < 0.001; boys: IRR = 4.0, P = 0.050]. Weekday dinner was the meal where girls were most likely to consume vegetables (OR = 3.0, P = 0.009) and when boys consumed the most vegetables (IRR = 30.9, P = 0.006). Fast food consumption was most likely for girls at dinner on the weekend (OR = 9.6, P = 0.042), whereas fast food intake for boys increased overall on the weekend (IRR = 3.6, P = 0.001). Intake of ‘other junk’ (e.g. crisps) peaked during school hours for girls (IRR = 7.2, P < 0.001) and sugar-sweetened beverage consumption increased for boys on the weekend (IRR = 3.3, P = 0.001). Overall, trends in fruit intake showed opposing times for high and low consumption compared to vegetable intake. Conclusions: These results represent the next step in using time of day and day of week consumption patterns to develop targeted, evidence-based dietary messages for interventions in overweight adolescents.